2007
DOI: 10.1007/s12032-007-0043-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of patients with stage III esophageal carcinoma: a single-center experience from Turkey

Abstract: Esophageal carcinoma is an extremely deadly disease, and prognosis is poor. We retrospectively evaluated stage III esophageal carcinoma patients in our center. Median age of the patients was 52. Men to women ratio were 3/1. Epidermoid carcinoma was the major histology. Incidence of esophageal carcinoma was higher in the distal and middle third of the esophagus. In 19 patients tumor size was more than 5 cm. In total of 17 of the patients were operated. About 58 patients were irradiated. About 45 of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In Ardabil, the low number of cases with a tumor in the esophagus’ upper third makes it difficult to derive any meaningful conclusion concerning this group. This result is consistent with a recent report from Turkey [18]. However, results from BC and other North American studies [1, 3] indicate that survival of patients with cancers in the upper, middle, and lower third of the esophagus are similar.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Ardabil, the low number of cases with a tumor in the esophagus’ upper third makes it difficult to derive any meaningful conclusion concerning this group. This result is consistent with a recent report from Turkey [18]. However, results from BC and other North American studies [1, 3] indicate that survival of patients with cancers in the upper, middle, and lower third of the esophagus are similar.…”
Section: Discussionsupporting
confidence: 92%
“…Patient characteristics include inherent and demographic characteristics such as age, sex, ethnicity, physical performance status, comorbidity, and immune status. These variables are usually unrelated to the presence of tumor but may have a profound impact on treatment choices [18]. The general treatment for esophageal and respectable gastric cancer was surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for studies of esophageal cancer, the location of tumors also showed differences in survival. Tumors in the middle 1/3 of the esophagus show worse survival in Turkey and Ardabil (Iran) [ 30 , 31 ], but tumors in the lower 1/3 of the esophagus are reported to have worse survival in BC and the United States[ 21 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…ESCC is an extremely fatal disease. In spite of major advancement in cancer treatment, prognosis is still poor (Ugur et al 2008). Precise mechanisms that underlie esophageal cancer tumorigenesis are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%